التقديم والتأخير عند الآلوسي في تفسيره "روح المعاني في تفسير القرآن العظيم والسبع المثاني" - Zakir, Muhammad; Baso Pallawagau; Abdul Rahim Muhammad (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2023)
Al-Takdi>m and al-Ta’khi>r are considered among the most important aspects of the miracle of the holy Qur’an, as every word in it comes in a distinctive way, and every change in this arrangement becomes a clear defect in the meaning. Despite the many secrets of al-Takdi>m and al-Ta’khi>r and its various types, many commentators did not pay attention to it and did not explain the secrets it has in its meaning. Speech, and most of their care in explaining what was presented was to say: Al-Takdi>m and al-Ta’khi>r are a form of care and attention, and for this reason some scholars blamed those who made the matter of al-Takdi>m easy and his status small; This is because they think that it is sufficient to say about everything that has been presented: it has been brought forward to be taken care of, and because mentioning it is more important. Al-Alusi explained and applied the miracle of the Qur’an, especially the al-Takdi>m and al-Ta’khi>r in its interpretation called the Spirit of Meanings in the Interpretation of the Great Qur’an and the Seven Repeated Verses, a book famous for its author’s interest in the rhetorical aspect of the Holy Qur’an. This research deals with the secrets of al-Takdi>m and al-Ta’khi>r in Al-Alusi’s interpretation, through the inductive approach. Where its secrets are extrapolated in its interpretation; The comparative approach is to compare all the opinions mentioned regarding the secrets of advancement and delay with other exegetical books. At the end of this research, the results come, the most important of which are: the secrets of al-Takdi>m and al-Ta’khi>r: attention to the advance and interest to the latter, specification, and al-Takdi>m because it is included in praise, and the declaration of equality, and al-Takdi>m in existence, and al-Takdi>m of the best, and al-Takdi>m the path of receiving revelation. The secrets of al-Takdi>m and al-Ta’khi>r are considered in the interpretation of Al-Alusi, as an extension of Abd al-Qahir al-Jurjani’s approach to systems theory in his book “Dala’il al-I’jaz”, Al-Alusi distinguished himself from Al-Zamakhshari, Al-Razi, Abu Hayyan, and other commentators who preceded him in many investigations into the secrets of al-Takdi>m and al-Ta’khi>r in the holy Qur’an.